Pengaruh Organizational Justice Dan Organizational Commitment Terhadap Intention To Stay Pada Karyawan Generasi Z Di Bank XXX Surabaya - Reynaldi Sudigdo (Journal of Creative Student Research, 2024)
The purpose of this study is to explain the effect of organizational justice on organizational commitment and intention to stay, and to explain the effect of organizational commitment on intention to stay. The design of this research is quantitative research. Research variables include: organizational justice, organizational commitment, and intention to stay. Data collection techniques using a questionnaire. The number of samples is 91 employees of Bank XXX in Surabaya. The data analysis technique in this study used a structural equation model with the PLS version 4 program. The findings of this study indicate that organizational justice is proven to have an effect on organizational commitment, but it is not proven to have a direct effect on intention to stay. Organizational commitment is proven to affect the intention to stay.